2016
DOI: 10.3892/ol.2016.5054
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of long non-coding RNA XIST predicts favorable prognosis of cervical squamous cell carcinoma subsequent to definitive chemoradiation therapy

Abstract: The present retrospective study aimed to examine the association between the expression of long non-protein-coding RNAs (lncRNAs) and clinical prognosis in the pretreatment formalin-fixed, paraffin-embedded (FFPE) tissue samples of cervical squamous cell carcinoma patients that underwent platinum-based chemoradiation therapy. Between 2001 and 2013, 49 consecutive patients with squamous cell cervical carcinoma were selected for the present study (median follow-up period, 44.1 months). The patients possessed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…Besides, XLOC_010588, XIST, LET, MEG3 were correlated to poor prognosis with the low expressions of lncRNAs in cervical cancer. With all the lncRNAs HOTAIR generate the highest HR of 5.28 [ 16 ]; by contrast, XIST exhibited the lowest HR of 0.27 [ 17 ]. Moreover, stratified analyses were performed using studies with the ethnicity.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, XLOC_010588, XIST, LET, MEG3 were correlated to poor prognosis with the low expressions of lncRNAs in cervical cancer. With all the lncRNAs HOTAIR generate the highest HR of 5.28 [ 16 ]; by contrast, XIST exhibited the lowest HR of 0.27 [ 17 ]. Moreover, stratified analyses were performed using studies with the ethnicity.…”
Section: Resultsmentioning
confidence: 99%
“…In hepatocellular carcinoma, the tumor suppressor activity of XIST was exerted by upregulating phosphatase and tensin homolog deleted on chromosome ten (PTEN) expression via miR‐181a (Chang et al, ), whereas the oncogenic role of XIST was exerted by upregulated MAPK1 expression via miR‐194‐5p (Kong et al, ). The underlying mechanism of XIST as a tumor suppressor in cervical squamous cell carcinoma is unexplored (Kobayashi et al, ); however, its oncogenic role in cervical squamous cell carcinoma was reported to attribute to the upregulation of RNA binding protein FUS through miR‐200a (Zhu et al, ). XIST upregulated programmed cell death protein 4 (PDCD4) expression by interacting with miR‐21‐5p and inhibited osteosarcoma cell growth and metastasis (Zhang & Xia, ).…”
Section: Discussionmentioning
confidence: 99%
“…39 In HNSCC cases, Xi reactivation can potentially be considered a marker of heterochromatin instability associated with poor prognosis as, much like cervical cancer, the disease may be associated with epigenetic modifications as well as oncoviruses that could alter the X-linked genes. 11,36,37 Thus, the destabilised genomic repertoire in HNSCC appears to be further undermined by epigenetic events. 39,40 However, before considering an association between the Barr body and HNSCC, a causal relation between X-linked TSGs and HNSCC development must be established.…”
mentioning
confidence: 99%
“…7,[11][12][13][14] This article focuses on reviewing variations in Barr body frequency in different malignancies and proposing its hypothetical involvement in HNSCC development. There is a need to further explore the role of sex chromosomes in HNSCC development in order to determine potential clinical implications.…”
mentioning
confidence: 99%
See 1 more Smart Citation